La sintesi passiva e le radici iletiche della sensibilità - Gonnella, Stefano (Philosophy Kitchen - Rivista di filosofia contemporanea, 2020)
In his Lessons on Passive Synthesis, Edmund Husserl develops a genetic-structural analysis of experience from perception, understood as the original way of intuitiveness and the primary source of knowledge. A novelty that emerges from Husserlian analyses is the fact that sensory data, rather than being “animated” according to apprehensive schemes, already present a primordial structuring of their own and the perceptive act that concerns them should not be understood as a conferral of meaning addressed to something that would be devoid of it, but rather as the clarification of a legality already functioning at a precategorial level, in the context of passive syntheses operated by pre-reflexive consciousness. Nevertheless, in order to phenomenologically admit the validity of this precategorical foundation, passivity, understood as the antepredicative sphere of experience and as the domain of ultimate and original evidence, must be distinguished from the mere perceptible intuition characteristic of the empirical self. The analytical reconnaissance of the conditions of possibility of experience therefore foreshadows an apparently insurmountable dilemma, because if the forms of experience do not come from the noetic intentionality of consciousness, but derive from experience itself, this means that, if we stick to the morphology of the Erlebnis designed by Husserl, a constitutive activity of meaning should be carried out by the hyle itself. However, the attribution to the hyle of “attractive” faculties, autonomous and prioritized with respect to the sphere of empirical sensitivity, poses the phenomenologist the further question of how to analytically grasp and, above all, conceptually understand this enigmatic animation of the “material” element of experience, having to avoid in principle assigning it any intentional competence or quality.